Emotion Regulation, Parasympathetic Function, and Psychological Well-Being - Brown, Ryan L.; Chen, Michelle A.; Paoletti, Jensine; Dicker, Eva E.; Wu-Chung, E. Lydia; LeRoy, Angie S.; Majd, Marzieh; Suchting, Robert; Thayer, Julian F.; Fagundes, Christopher P. (Frontiers in Psychology, 2022)
The negative emotions generated following stressful life events can increase one’s risk of depressive symptoms and promote higher levels of perceived stress. The process model of emotion regulation can help distinguish between adaptive and maladaptive emotion regulation strategies to determine who may be at the greatest risk of worse psychological health across the lifespan. Heart rate variability (HRV) may affect these relationships as it indexes aspects of self-regulation, including emotion and behavioral regulation, that enable an individual to dynamically adapt to the changing demands of both internal and external environments. In this study, we expected individual differences in resting vagally mediated HRV to moderate the influence of emotion regulatory strategies among our sample of 267 adults. We found support for the hypothesis that higher vagally mediated HRV buffers against the typical adverse effects of expressive suppression when evaluating depressive symptoms and found weak support when considering perceived stress. There was no evidence for an interaction between cognitive reappraisal and vagally mediated HRV but there was a significant, negative association between cognitive reappraisal and depressive symptoms and perceived stress. Future work may determine if intervening on either emotion regulation strategies or HRV may change these within-persons over time.